AN INTERACTIVE MOBILE AUGMENTED REALITY PLAYBOOK: READING PROPHET NOAH AND THE FLODD STORY. - HASNI, NOR HAMIZAH (IRC, 2019)
We’re heading to Industrial 4.0 but there is still shortage of Islamic learning studies in interactive way like other subject’s book we have seen which give in consideration to the implementation of this project. In this project, will integrate Augmented Reality (AR) component in the Islamic education children’s storybook. The focus will be on Prophet’s Noah and The Flood Storybook which will merge the mixed reality into a physical book, this will give an opportunity for the user to interact with the virtual and reality experience in perfectly if the user never has experience using AR. This project will use a vision-based tracking method to overlay the virtual models for example 2D animation video and 3D object on the physical book and create an AR scene with different story in every pages of the physical book. The user will experience the immersion like Virtual Reality (VR) environment when they view the AR scene. It is slightly different from immersive VR; the AR interfaces will allow the users to view the real world at the real time world tracking as virtual imagery that will attach to the particular marker (tracked location) of the chosen objects. The project will be tested on an audience of randomly selected preschool children aged 5 years old.